Mangroves are Machines: Ecolinguistics Study - Wardana, Muhammad Kiki; Widayati, Dwi; Mulyadi, Mulyadi; Zein, T. Thyrhaya (Proceeding International Conference on Malay Identity, 2024)
This study explores the conceptual metaphor of "Mangroves are machines" within the framework of ecolinguistics, analyzing how language shapes our understanding of mangroves and their role in environmental conservation. This research employs a conceptual metaphor theory to dissect how this metaphor influences public perception, policy discourse, and conservation efforts. The data were taken from discourses circulated within the mangrove conservation. The study reveals that languages disseminated within the conservation area use some specific linguistics expression that eventually led to the comprehension that mangroves can be easily understood in the concept of machineries. This metaphor not only underscores the ecological importance of mangroves but also promotes a mechanistic view of nature that can influence both positive and negative attitudes towards conservation. The findings suggest that while the metaphor effectively communicates the critical functions of mangroves, it also exposes variations of concepts in order to make the term of mangrove more familiar.